Cost analysis of VATS approaches - Brunelli, Alessandro (Video-Assisted Thoracic Surgery; Vol 1 (October 2016): Video-Assisted Thoracic Surgery, 2016)
Video-assisted thoracoscopic surgery has become the recommended approach for pulmonary anatomic resections performed for early stage lung cancer. Several retrospective studies have shown that VATS is associated with reduced incidence of complications and shorter hospital stay compared to open surgery. This translates into reduced postoperative hospital costs. A number of investigators have analysed the impact of this surgical approach on hospital costs compared to thoracotomy. In general they found that VATS intraoperative costs are higher owing to increased use of disposables, whilst postoperative costs are lower owing to shorter hospital stay. Whether this translates into an overall cost saving for the provider depends on the local financial setting. Other authors have tried to identify factors associated with cost variability after VATS lobectomy. The objective is to find areas or groups of patients, where to implement strategies of practice and financial improvement. In addition, the identification of patient and procedure related factors associated with increased costs should be taken into account when defining reimbursement tariffs for specific procedures. We reviewed the existing literature about the financial aspects of VATS lobectomy.